2018
DOI: 10.1056/nejmoa1808788
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Outcomes after PCI Strategies in Cardiogenic Shock

Abstract: Among patients with acute myocardial infarction and cardiogenic shock, the risk of death or renal-replacement therapy at 30 days was lower with culprit-lesion-only PCI than with immediate multivessel PCI, and mortality did not differ significantly between the two groups at 1 year of follow-up. (Funded by the European Union Seventh Framework Program and others; CULPRIT-SHOCK ClinicalTrials.gov number, NCT01927549 .).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
193
3
20

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 346 publications
(222 citation statements)
references
References 26 publications
6
193
3
20
Order By: Relevance
“…Unfortunately, despite these efforts, CS mortality remains unacceptably high, and there are no prospective randomized trials showing that percutaneous mechanical circulatory support devices change the mortality in this clinical state . It has been difficult to prove therapeutic benefit, in part, because CS patients are a heterogeneous population, and prognosis may vary widely based on etiology, severity of illness and comorbidities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, despite these efforts, CS mortality remains unacceptably high, and there are no prospective randomized trials showing that percutaneous mechanical circulatory support devices change the mortality in this clinical state . It has been difficult to prove therapeutic benefit, in part, because CS patients are a heterogeneous population, and prognosis may vary widely based on etiology, severity of illness and comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, despite these efforts, CS mortality remains unacceptably high, and there are no prospective randomized trials showing that percutaneous mechanical circulatory support devices change the mortality in this clinical state. [3][4][5][6][7][8][9] It has been difficult to prove therapeutic benefit, in part, because CS patients are a heterogeneous population, and prognosis may vary widely based on etiology, severity of illness and comorbidities. CS encompasses a spectrum spanning from those at high risk of developing shock due to isolated myocardial dysfunction to those critically ill patients with severe multi-organ dysfunction and hemodynamic collapse to those with ongoing cardiac arrest.…”
Section: Introductionmentioning
confidence: 99%
“…still failed to recover from malignant complication. 4 There is no doubt that understanding the mechanism and pathology will provide new clues for clinical treatment.…”
mentioning
confidence: 99%
“…20 However, CL-PCI was associated with higher rates of repeat revascularization and readmission for heart failure in the long run. 20 This could possibly be due to the fact that MV-PCI leads to improved long-term ventricular function and subsequent reduced rates of heart failure. However, we do not have any definitive data to support this hypothesis and our pooled analysis did not show any benefit in secondary long-term efficacy end points with MV-PCI.…”
Section: Discussionmentioning
confidence: 99%
“…19 1-year outcomes of this landmark trial were recently published and showed that CL-PCI (with the option of staged revascularization of non-culprit lesions) was associated with better short-term outcomes and similar long-term mortality, compared to immediate MV-PCI, thus challenging the existing guidelines. 20 On the basis of this trial, the ESC downgraded MV-PCI in CS from a class II A to a class III B recommendation, in the recently released 2018 ESC guidelines. 21 In contrast to CULPRIT-SHOCK, recently published real world data from the large-scale, KAMIR-NIH registry study showed a significantly lower risk of all-cause mortality at 1 year with MV-PCI, compared to CL-PCI in patients with AMI and CS.…”
Section: Introductionmentioning
confidence: 99%